PROKRASTINASI AKADEMIK: DAPATKAH KONSELING COGNITIVE RESTRUCTURING MENGATASINYA? - Huwae, Inggrid Beatrix; Abdullah, Sri Muliati (JIP (Jurnal Intervensi Psikologi), 2026)
ABSTRACT: Academic procrastination is an individual's behavior in the form of postponing the completion of academic tasks. Academic procrastination risks becoming a recurring behavioral pattern that increasingly worsens students’ academic performance and mental well-being. This study aims to determine the effect of group counseling with cognitive restructuring techniques on academic procrastination behavior. This research involved 10 students of SMA “X” with academic procrastination behavior. Data collection was carried out using an academic procrastination scale and interviews. This study employed a quasi-experimental pretest-posttest control group design. Data analysis using the U Mann Whitney test showed that there was no significant difference in academic procrastination levels between the experimental group and the control group. In conclusion, group counseling with cognitive behavioral techniques using cognitive restructuring did not significantly affect the academic procrastination behavior of SMA “X” students.  Keywords: Academic procrastination, cognitive restructuring.  ABSTRAK: Prokrastinasi akademik adalah perilaku individu berupa penundaan terhadap pengerjaan maupun penyelesaian tugas akademik. Prokrastinasi akademik berisiko menjadi pola perilaku berulang yang semakin memperburuk prestasi akademik hingga kondisi mental siswa. Penelitian ini bertujuan untuk mengetahui pengaruh konseling kelompok cognitive behavioral dengan teknik cognitive restructuring terhadap perilaku prokrastinasi akademik. Penelitian ini melibatkan 10 siswa SMA “X” dengan perilaku prokrastinasi akademik. Pengumpulan data dilakukan dengan skala prokrastinasi akademik dan wawancara. Penelitian ini menggunakan desain penelitian kuasi eksperimen dengan pretest posttest control group design. Analisis data dengan uji U Mann Whitney menunjukkan hasil bahwa tidak ada perbedaan yang signifikan terkait tingkat prokrastinasi akademik antara kelompok eksperimen dan kelompok kontrol. Kesimpulannya, konseling kelompok kognitif perilaku dengan teknik restrukturisasi kognitif tidak berpengaruh secara signifikan terhadap perilaku prokrastinasi akademik siswa SMA “X”.  Kata kunci: Prokrastinasi akademik, restrukturisasi kognitif.